Pemanfaatan Foto Udara Multispektral Untuk Sidik Cepat Kerapatan Tutupan Vegetasi Di Wilayah Perkotaan - Rahmadana, Aries Dwi Wahyu (Universitas Negeri Yogyakarta, 2023)
Current technology enables NDVI analysis of multispectral aerial photographs, providing fast, detailed actual vegetation cover information. However, no study shows the best threshold value for mapping vegetation cover in urban areas. This study aims 1) to compare the area of vegetation cover on a semi-detailed and detailed scale, and 2) to determine the best NDVI threshold for mapping vegetation cover in urban areas. This study uses multispectral aerial photographs and Sentinel-2 satellite imagery (positioned as the baseline). Aerial imagery and photographs are processed for visible, red, and NIR bands. Band image processing and aerial photographs were used for NDVI analysis. The results show that the best threshold is at NDVI 0.2. The results of the identification of vegetation cover with Sentinel-2 imagery showed an area of 6.37 hectares or 28,2%, while the aerial photos resulted in an area of 11.4 hectares or 50,5%. The difference in area between the two spatial data is due to differences in the resolution of Sentinel-2 imagery with aerial photographs, 4 cm, and 10 m.